Pengaruh Board Of Directors Terhadap Cost Of Capital Dengan Risk Disclosure Sebagai Variabel Mediasi - Glady, Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this research is to obtain empirical evidence about the effects of board of directors on cost of capital in manufacturing industries listed in Indonesian Stock Exchange during the period of 2017. This research used 25 samples of manufacturing companies that have been previously selected using purposive sampling method with total of 25 data for one year. The data used were secondary data in the form of financial information and non-financial information from the annual reports and forecasting EPS data from marketscreener website. This research data was processed using Smart PLS 3. The result of this research shows that risk disclosure doesn’t have a significant effect on cost of capital. Board of directors also does not have a significant effect on cost of capital, directly or indirectly through the mediator